AASHTO LRFD bridge design specifications. (American Association of State Highway and Transportation Officials, 2010)
AASHTO will not be releasing an SI units version of the 5th edition of this publication. The provisions of these Specifications are intended for the design, evaluation, and rehabilitation of both fixed and movable highway bridges. The design provisions of these Specifications employ the Load and Resistance Factor Design (LRFD) methodology. The factors have been developed from the theory of reliability based on current statistical knowledge of loads and structural performance. Seismic design shall be in accordance with either the provisions in these Specifications or those given in the AASHTO Guide Specifications for LRFD Seismic Bridge Design. Construction specifications consistent with these design specifications are the AASHTO LRFD Bridge Construction Specifications. Unless otherwise specified, the Materials Specifications referenced herein are the AASHTO Standard Specifications for Transportation Materials and Methods of Sampling and Testing. Mechanical, electrical, and special vehicular and pedestrian safety aspects of movable bridges, however, are not covered.
Keywords: Bridges -- Design and construction -- Specifications -- United States.; Bridges -- Live loads -- Specifications -- United States.; Bridges -- Maintenance and repair -- Specifications -- United States.; elektronické knihy; electronic books